Acute effects of cinacalcet on arterial stiffness and ventricular function in hemodialysis patients: A randomized double-blinded crossover study. Issue 21 (May 2017) - Poulin, Aurélie; Bellemare, Pierre-Luc; Fortier, Catherine; Mac-Way, Fabrice; Desmeules, Simon; Marquis, Karine; Gaudreault, Valérie; Lebel, Marcel; Agharazii, Mohsen
Abstract: Background: Serum calcium concentration (Ca) plays an essential role in a vascular muscle tone and myocardial contractility. Previously, we showed that acutely lowering Ca by hemodialysis reduced arterial stiffness. Cinacalcet is a calcimimetic that lowers Ca and parathyroid hormone (PTH). The aim of the present study was to examine whether acute lowering of Ca by cinacalcet improves vascular stiffness and myocardial diastolic dysfunction. Method: This is a double-blinded randomized placebo-controlled crossover study that included 21 adult patients with end-stage kidney disease undergoing chronic hemodialysis. Subjects were assigned to placebo-cinacalcet (30 mg) or cinacalcet–placebo sequence. After each treatment period (7 days), aortic, brachial, and carotid stiffness were determined by examining carotid-femoral pulse wave velocity (cf-PWV), carotid-radial PWV (cr-PWV), and carotid distension. A central pulse wave profile was determined by radial artery tonometry and cardiac function was evaluated by echocardiography. Results: Cinacalcet reduced PTH (483 [337–748] to 201 [71–498] ng/L, P < .001) and ionized Ca (1.11 [1.08–1.15] to 1.05 [1.00–1.10] mmol/L, P = .04). Cinacalcet did not reduced cf-PWV significantly (12.2 [10.4–15.4] to 12.2 [11.0–14.6] m/s, P = .16). After adjustments for mean blood pressure, sequence, carryover, and treatment effects, cf-PWV was not significantly lowered by cinacalcet (–0.35 m/s, P = .139). There were no significant changes in central blood pressures, brachial and carotid stiffness, and echocardiographic parameters. Conclusion: In this study, 30 mg daily cinacalcet for 1 week did not have any significant impact on peripheral and central blood pressures, arterial stiffness parameters, or cardiac function (NCT01250405).